A Blue-Light-Emitting BODIPY Probe for Lipid Membranes - Bacalum, Mihaela; Wang, Lina; Boodts, Stijn; Yuan, Peijia; Leen, Volker; Smisdom, Nick; Fron, Eduard; Knippenberg, Stefan; Fabre, Gabin; Trouillas, Patrick; Beljonne, David; Dehaen, Wim; et al. (Langmuir, 2016)
Here we describe a new BODIPY-based membrane probe (1) that provides an alternative to dialkylcarbocyanine dyes, such as DiI-C18, that can be excited in the blue spectral region. Compound 1 has unbranched octadecyl chains at the 3,5-positions and a meso-amino function. In organic solvents, the absorption and emission maxima of 1 are determined mainly by solvent acidity and dipolarity. The fluorescence quantum yield is high and reaches 0.93 in 2-propanol. The fluorescence decays are well fitted with a single-exponential in pure solvents and in small and giant unilamellar vesicles (GUV) with a lifetime of ca. 4 ns. Probe 1 partitions in the same lipid phase as DiI-C18(5) for lipid mixtures containing sphingomyelin and for binary mixtures of dipalmitoylphosphatidylcholine (DPPC) and dioleoylphosphatidylcholine (DOPC). The lipid phase has no effect on the fluorescence lifetime but influences the fluorescence anisotropy. The translational diffusion coefficients of 1 in GUVs and OLN-93 cells are of the same order as those reported for DiI-C18. The directions of the absorption and emission transition dipole moments of 1 are calculated to be parallel. This is reflected in the high steady-state fluorescence anisotropy of 1 in high ordered lipid phases. Molecular dynamic simulations of 1 in a model of the DOPC bilayer indicate that the average angle of the transition moments with respect to membrane normal is ca. 70°, which is comparable with the value reported for DiI-C18.
Keywords: Unilamellar Liposomes; unilamelární lipozómy; buněčná membrána; Spectrometry, Fluorescence; Fluorescence Polarization; sloučeniny boru; fluorescenční spektrometrie; krysa rodu Rattus; Alkanesulfonates; zvířata; buněčné linie; simulace molekulární dynamiky; alkylsulfonany; fluorescenční barviva; Cell Line; Fluorescent Dyes; fluorescenční polarizace; Molecular Dynamics Simulation; Boron Compounds; Rats; Animals; Cell Membrane